The interaction of titanium films with oxygen over a wide range of pressures and exposures - Kandasamy, K.; Surplice, N.A. (Elsevier B.V., 1980)
The interaction of titanium films with oxygen has been studied by observing their change of resistance R and workfunction phi over the range of gas pressures from UHV to 5 Torr and exposures from 0-106 Torr s. The changes in R during the fast stage of the interaction indicated that oxygen dissolved in the Ti lattice in a few seconds. The maximum increase of 1.1 eV in phi was reached at an equilibrium pressure p approximately 10-4 Torr. When p was raised above 10-4 Torr phi decreased by 0.4-0.8 eV which suggests that crystals of an oxide were being formed on the film. For p>1 Torr and exposure >104 Torr s there were further changes approximately=0.2 eV in phi which showed that the oxide was not stable. There was also a change approximately=0.1 eV due to a weakly bound adspecies which was desorbed when the gas was pumped off.